2017
DOI: 10.3168/jds.2016-11888
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Evaluating nuclear magnetic resonance spectroscopy for determining body composition in Holstein dairy calves using deuterium oxide dilution methods

Abstract: Deuterium oxide (DO) dilution methods have been used to assess body composition in live animals. Estimated body water content can be used to predict body fat and protein, and thus, the amount of energy reserves. It is an alternative method to direct chemical analysis and considered a noninvasive technique that is economical and repeatable. Deuterium oxide use is considered easy, safe, and accurate; however, the traditional methods of analyzing DO are expensive, tedious, and time consuming. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Water makes up between 56% and 81% of total body weight in the dairy cow 25 and between 68% and 72% in the preruminant calf. 26 Water is essential for the transport of substances around the body, temperature regulation, insulation, and removal of wastes. As described earlier, water is essential for rumen microbial development in the preruminant calf and ultimately critical in the conversion of the calf from non-ruminant to ruminant (see calf and heifer section).…”
Section: Watermentioning
confidence: 99%
“…Water makes up between 56% and 81% of total body weight in the dairy cow 25 and between 68% and 72% in the preruminant calf. 26 Water is essential for the transport of substances around the body, temperature regulation, insulation, and removal of wastes. As described earlier, water is essential for rumen microbial development in the preruminant calf and ultimately critical in the conversion of the calf from non-ruminant to ruminant (see calf and heifer section).…”
Section: Watermentioning
confidence: 99%
“…The amount of MR fed remained consistent throughout the entirety of the experiment, and refusals were measured at both a.m. and p.m. feedings. Feeding rates were based on previous research conducted at our university ( Guindon et al, 2015 ; Chapman et al, 2017a , b ; Aragona et al, 2020 ). While some studies at our institution have indicated that calves fed MR at a higher rate present with greater gains and feed efficiency during the preweaning period ( Guindon et al, 2015 ; Chapman et al, 2017a ), these studies have also revealed lower starter intakes during the preweaning and weaning phases ( Guindon et al, 2015 ; Chapman et al, 2017a ), poorer nitrogen efficiency ( Chapman et al, 2017a ), and greater cortisol levels at weaning, suggestive of more stress due to removal of MR ( Guindon et al, 2015 ), compared with the control group.…”
Section: Methodsmentioning
confidence: 99%
“…The requirement of net protein for weight gain (NPg) was estimated by regression equation of retained protein in shrunk weight gain (g/kg of daily EBW 0.75 ) on protein intake (g/kg of daily EBW 0.75 ) (CHIZZOTTI et al, 2007).…”
Section: Nutritional Requirementsmentioning
confidence: 99%
“…The use of deuterium dilution for beef cattle began in the 1980s (ARNOLD et al, 1985;LEME et al, 1994;GOMES et al, 2012) and also has been used for studies with swine (ZHANG et al, 2017), sheep and goats (AL-RAMAMNEH, et al;2010),dairy cattle (CHAPMAN et al, 2017;SCHAFF et al, 2017) and equine (DUGDALE et al, 2011;FERJAK et al, 2017).…”
Section: Introductionmentioning
confidence: 99%